Transitivity in the Bima Language (e-Journal of Linguistics, 2023)
Transitivity is one of the syntactical studies that is affected bymorphology. This article describes how transitivity is expressed andhow transitive are the verbs in the constructions of clauses in the BimaLanguage. Transitivity in the Bima Language is mostly expressed usingbasic verbs which can be syntactically used as verbs in clauses. Apartfrom this, prefix ka- with its variant ca- is used to derive transitive fromintransitive verbs and nonverbal categories. Meanwhile, particle kai andwea are used to derive ditransitive from transitive verbs. The transitivityof verbs in the Bima Language varies from one to another. Whether theverbs are said to have high or low transitive, it depends on how theyfulfill the transitive parameter (Hooper and Thompson, 1989). Form 10parameters of transitivity, there are four parameters which fit the BimaLanguage transitivity, such as participant (agents and patients),affectedness of patient, potency of agent, and volitionality. Theconstructions which are considered as high transitive is that if theconstructions use action verbs rather than state verbs and mental verbs.It is found out that action verbs can cause the agents of the clause totake control on the activities, can affect the patients, and intensively cancause the agent to do the activities expressed by the verbs deliberatelyand intensively.
Keywords: transitivity; high transitive; low transitive